2020
DOI: 10.1091/mbc.e19-10-0563
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic morphogenesis of a pioneer axon in Drosophila and its regulation by Abl tyrosine kinase

Abstract: Live imaging of an axon in its native tissue shows that its growth is protrusive and occurs by stabilization of selected filopodia. Guidance signaling, however, for example, via Abl tyrosine kinase, does not control these morphological properties directly but rather controls actin distribution to determine where filopodial dynamics can occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 42 publications
8
54
0
Order By: Relevance
“…Therefore, we favor a model of Htt acting as an inhibitor of Abl kinase activity during normal MB axonal growth ( Fig 7 ). Abl activity in axons needs to be maintained within rather narrow limits [ 32 , 33 ]. These two recent studies show that either increase or decrease of Abl activity cause disorganization of actin structure in the growth cone and prevent the orderly oscillation of growth cone actin that is the motor for growth cone advance and thus axon extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we favor a model of Htt acting as an inhibitor of Abl kinase activity during normal MB axonal growth ( Fig 7 ). Abl activity in axons needs to be maintained within rather narrow limits [ 32 , 33 ]. These two recent studies show that either increase or decrease of Abl activity cause disorganization of actin structure in the growth cone and prevent the orderly oscillation of growth cone actin that is the motor for growth cone advance and thus axon extension.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the precise level of Abl activity is critical to its axonal function, with loss- and gain-of-function both leading to severe defects in neural patterning [ 29 31 ]. Recent experiments revealed the cell biological and biophysical basis of this relationship, showing that either increased or decreased levels of Abl activity induce disorder in growth cone actin and thereby greatly augment the frequency of stochastic errors in growth and guidance [ 32 , 33 ]. Of particular relevance here, Abl has been implicated in axonal arborization and growth in the Drosophila brain [ 34 ], including the MBs [ 5 ], though the precise role of Abl in normal MB development has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…In the accompanying paper (Clarke et al, 2020), however, we have shown that a pioneer axon of Drosophila, TSM1, like many pioneer axons in the compliant medium of developing tissue, advances in a mode that appears to be fundamentally different: a protrusive mode of growth dependent on selective stabilization of a subset of appropriately oriented projections and disassembly of nonselected projections. It is quite unclear how, and whether, the familiar adhesive mechanisms would apply to this very different machine.…”
Section: Introductionmentioning
confidence: 93%
“…This view, together with the results of the accompanying paper (Clarke et al, 2020), reveals that any serious analysis of the mechanism of axon growth and guidance must be grounded in the biophysics of the actin network of the growth cone: its distribution, organization, and dynamics. With this in mind, we reasoned that the key to ascertaining the mechanism of TSM1 growth and guidance was to use high-resolution live imaging to monitor in real time the actin cytoskeleton of the advancing growth cone as we manipulate experimentally a cytoplasmic signaling module that implements axon growth and guidance signals, the Abelson (Abl) tyrosine kinase.…”
Section: Introductionmentioning
confidence: 97%
“…The developing Drosophila wing has long been a model for axon growth and neuronal pathfinding and differentiation 49,50 . More recently, spinning disk confocal microscopy was used to dissect the role of cytoskeletal organization and dynamics in shaping the morphogenesis and growth of the TSM1 pioneer sensory neuron axon in explanted earlypupal wing imaginal discs 51,52 . In those experiments, phototoxicity and photobleaching limited imaging duration to ~30 volumes, with image volumes acquired every 3 minutes.…”
Section: Bio-133 Enables Subcellular Imaging Segmentation and Trackmentioning
confidence: 99%